The Effect Of Supervision Implementation Of Work Units On Using Hospital Information Systems At dr. Soepraoen Hospitals Malang - Suwito Suwito; Fita Rusdian Ikawati; Anis Ansyori; Silvia Intan Wardani (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2022)
This study aims to find the effect of the implementation of work unit supervision on the use of hospital information systems in dr. Soepraoen Malang Hospital. The research method used was quantitative with a cross sectional study approach. The location in this study is Kindergarten Hospital. II dr. Soepraoen Malang. The study was conducted from October to November 2020 involving 59 samples. Data processing was performed using the SPSS application. The results showed that there was a positive and significant influence between the implementation of work unit supervision on the use of hospital information.